Research Advances on Matrine - Sun, Xiao-Ying; Jia, Li-Yi; Rong, Zheng; Zhou, Xin; Cao, Lu-Qi; Li, Ai-Hong; Guo, Meng; Jin, Jie; Wang, Yin-Di; Huang, Ling; Li, Yi-Heng; He, Zhong-Jing; et al. (Frontiers in Chemistry, 2022)
Matrine is an alkaloid extracted from traditional Chinese herbs including Sophora flavescentis, Sophora alopecuroides, Sophora root, etc. It has the dual advantages of traditional Chinese herbs and chemotherapy drugs. It exhibits distinct benefits in preventing and improving chronic diseases such as cardiovascular disease and tumors. The review introduced recent research progresses on extraction, synthesis and derivatization of Matrine. The summary focused on the latest research advances of Matrine on anti-atherosclerosis, anti-hypertension, anti-ischemia reperfusion injury, anti-arrhythmia, anti-diabetic cardiovascular complications, anti-tumor, anti-inflammatory, anti-bacterium, anti-virus, which would provide new core structures and new insights for new drug development in related fields.